2015
DOI: 10.1111/ejn.13103
|View full text |Cite
|
Sign up to set email alerts
|

Chemogenetic manipulation of ventral pallidal neurons impairs acquisition of sign‐tracking in rats

Abstract: Cues associated with rewarding events acquire value themselves as a result of the incentive value of the reward being transferred to the cue. Consequently, presentation of a reward-paired cue can trigger reward-seeking behaviors towards the cue itself (i.e., sign-tracking). The ventral pallidum (VP) has been demonstrated to be involved in a number of motivated behaviors, both conditioned and unconditioned. However, its contribution to the acquisition of incentive value is unknown. Using a discriminative autosh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
64
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 36 publications
7
64
0
Order By: Relevance
“…Another explanation involves differences in the methods used to manipulate RSC in the two experiments (i.e., permanent electrolytic or neurotoxic lesions in Experiment 1, chemogenetics in Experiment 2). Specifically, in our laboratory, we have found that DREADD expression is not evident in all cells in the target region, and not all infected cells are inhibited by CNO (Chang et al 2015). Thus, the DREADD manipulation in Experiment 2 may be tantamount to a "partial lesion" of the RSC, which may leave context fear memory intact.…”
Section: Discussionmentioning
confidence: 82%
See 1 more Smart Citation
“…Another explanation involves differences in the methods used to manipulate RSC in the two experiments (i.e., permanent electrolytic or neurotoxic lesions in Experiment 1, chemogenetics in Experiment 2). Specifically, in our laboratory, we have found that DREADD expression is not evident in all cells in the target region, and not all infected cells are inhibited by CNO (Chang et al 2015). Thus, the DREADD manipulation in Experiment 2 may be tantamount to a "partial lesion" of the RSC, which may leave context fear memory intact.…”
Section: Discussionmentioning
confidence: 82%
“…This viral vector contained a gene for a synthetic inhibitory G-protein-coupled receptor (hM4Di) (Armbruster et al 2007;Urban and Roth 2014) that suppresses neural activity when activated by systemic injection of clozapine-n-oxide (CNO; e.g., Robinson et al 2014;Chang et al 2015). Control rats were infused with a viral vector (AAV-hSyn-GFP) that did not contain the hM4Di receptor (n ¼ 8; Group GFP).…”
mentioning
confidence: 99%
“…For instance, a current question in the field of reward learning is how complex Pavlovian motivational behaviors (e.g., sign-tracking) are acquired over weeks. To address that, KSS has used DREADDs to transiently inactivate target brain areas each day during a two-week acquisition period (Chang, Todd, Bucci, & Smith, 2015). In our and others' experiences, CNO has been repeatedly used in the same animals to acutely activate DREADDs (with CNO doses up to 20 mg/kg by SVM) repeatedly, without evidence of decaying effects, hangover-like effects, or lingering behavioral issues that may confound subsequent behavior(Mahler, Vazey, & Aston-Jones, 2013; Mahler et al, 2014; S. Robinson et al, 2014).…”
Section: Section 1 – Advantages For Behavioral Neurosciencementioning
confidence: 99%
“…KSS and DJB have found a similar circa 60% suppression of activity in awake-behaving animals expressing hM4Di in the same pallidal structure upon i.p. CNO administration (Chang, Todd, Bucci, et al, 2015). In that work, an average onset latency of the change in firing was 12 minutes after CNO delivery and response offset (i.e., return to baseline) occurred at ca.…”
Section: Section 1 – Advantages For Behavioral Neurosciencementioning
confidence: 99%
See 1 more Smart Citation